Teaching Tomorrow: Global Education in the Age of Technology - Sayed Mahbub Hasan Amiri; Md. Mainul Islam; Naznin Akter; Sayed Majhab Hasan Amiri (Advanced Journal of STEM Education, 2025)
This article explores the transformative impact of technology on global education and curriculum development in the 21st century. It examines how digital tools such as coding, artificial intelligence, and virtual learning environments are reshaping traditional educational models to meet the demands of a rapidly evolving knowledge economy. Through a comparative qualitative study of diverse international contexts, including developed and developing countries, the article highlights emerging global trends such as the integration of digital literacy, hybrid learning environments, and flexible curriculum design aligned with Sustainable Development Goal 4 (SDG 4). The research identifies significant challenges related to equity, access, and cultural relevance, underscoring the persistent digital divide and institutional resistance. Drawing on theoretical frameworks like constructivist learning and Technological Pedagogical Content Knowledge (TPACK), the study advocates for adaptable and inclusive education systems that blend local needs with global competencies. The article concludes with recommendations emphasizing holistic curriculum development, investment in teacher training, equitable access policies, and international collaboration in educational technology innovation. These insights aim to inform policymakers, educators, and stakeholders seeking to harness technology for quality education worldwide. Ultimately, the paper calls for a coordinated global effort to ensure that educational technology contributes to equitable, forward-looking learning environments that prepare learners for future societal and economic challenges.